HUBUNGAN TINGKAT PENGETAHUAN PENDERITA DIABETES MILITUS DENGAN KETERKENDALIAN GULA DARAH DI POLIKLINIK RS PERJAN Dr. M. DJAMIL PADANG TAHUN 2003 - Isniati Isniati (Jurnal Kesehatan Masyarakat Andalas, 2007)
Diabetes Mellitus brings health and economic consequences to the patients. The chronic complications lead to difficulties in its management. A good and rational management could diminish the difficulties. A research has been done with cross sectional design on April 2003 towards 61 respondents. Research instruments are questionnaire, fasting and 2nd post-prandial blood sugar concentration. Data processing and analysing was using SPSS programme software for Windows 9.05 version. The result shows that most of fasting blood sugar concentration has poor 2hr post-prandial blood sugar concentration, while having sufficient knowledge about Diabetes Mellitus, dieting, exercising and anti-diabetic drugs. An approach is needed to obtain what kinds of effort could be carried out to lower or stabilize blood sugar concentration. Further research should focuses on other factors contributing in blood sugar concentration control, such as; attitude, tradition, faith/belief, etc.